Становлення та трансформація фінансової системи в Україні (XVIII-XX століття): історико-правове дослідження : автореф. дис. - Карп’як, О. О.; Karpiak, O. O.; Карпяк, О. О. (Харків : Харківський національний університет внутрішніх справ, 2021)
Досліджено становлення та трансформація фінансової системи в Україні. Всебічно охарактеризовано становлення та розвиток фінансово-правових відносин на українських територіях у їх історико-правовому осяганні. Визначено специфіку становлення окремих фінансових зобов’язань та їх значення у державній політиці в залежності від хронологічних рамок, а також інститут державного фінансового контролю як форму забезпечення фінансової політики.

In the dissertation research the formation and transformation of the financial system in Ukraine is comprehensively considered. The formation and development of financial and legal relations in the Ukrainian territories in their historical and legal comprehension comprehensively described. The specifics of the formation of individual financial obligations and their importance in public policy depending on the chronological framework, as well as the institution of public financial control in the form of financial policy. The introduction to the dissertation presents the relevance of the topic, defines its relationship with scientific programs, plans, topics, purpose and objectives of the study, its object and subject, research methods, reveals the scientific novelty and practical significance of the results, provides data on their testing and work structure. The scientific novelty of the obtained results is that for the first time in legal science an attempt was to provide a conceptual justification and historical and legal analysis of the process of formation and transformation of the financial system in Ukraine in the XVIII - XX centuries. Within the dissertation a number of scientific conceptual provisions, conclusions and generalizations substantiated, which are important for the historical and legal science of Ukraine and can be taken into account in the process of Ukrainian state formation, in particular argued that the formation and transformation of the financial system was not determined by the linear nature, and the lack of clear and balanced mechanisms of public financial policy characterized it as a spontaneous activity of certain public authorities aimed at obtaining financial resources to cover the costs of a government body. Providing it with the necessary material and technical resources, and in some cases ‒ financing a separate key function of the state, such as waging war or maintaining certain segments of society.

Исследованы становление и трансформация финансовой системы в Украине. Всесторонне охарактеризованы становление и развитие финансово-правовых отношений на украинских территориях в их историко-правовом постижении. Определена специфика становления отдельных финансовых обязательств и их значение в государственной политике в зависимости от хронологических рамок, а также институт государственного финансового контроля как форму обеспечения финансовой политики. Констатировано, что становление и трансформация финансовой системы в исследуемый период не определялась линейным характером, а отсутствие четких и взвешенных механизмов государственной финансовой политики характеризовали ее как стихийную деятельность отдельных органов государственной власти направленную на получение денежных ресурсов для покрытия расходов того или иного органа государственного управления, а также обеспечение его необходимыми материально-техническими ресурсами, а в отдельных случаях  финансирование отдельной ключевой функции государства, например ведения войны или содержание определенных слоев общества. Определено, что формирование и трансформация структурных элементов финансовой системы осуществлялось через призму абстрактных форм правового регулирования общественных отношений и их видоизменения в специализированные функции отдельных органов государственного управления по обеспечению финансового контроля.
Автореферат дисертації на здобуття наукового ступеня кандидата юридичних наук
The formation and transformation of the financial system in Ukraine (XVIII-XX centuries): historical and legal research
Карп’як О. О. Становлення та трансформація фінансової системи в Україні (XVIII-XX століття): історико-правове дослідження : автореф. дис. ... канд. юрид. наук : 12.00.01 / Карп’як Оксана Орестівна; МВС України, Харк. нац. ун-т внутр. справ. - Харків, 2021. - 24 с.
Keywords: Держава і право. State and Law. Государство и право; Автореферати дисертацій. Abstracts of Theses. Авторефераты диссертаций; Україна. Ukraine. Украина; Історія. History. История; 12.00.01; Фінансове право. Бюджетне право. Банківське право. Financis Law. Budget Law. Banking Law. Финансовое право. Бюджетное право. Банковское право; історико-правовий аналіз; historical and legal analysis; историко-правовой анализ; фінанси; finances; финансы; фінансова система; financial system; финансовая система; financial activity; фінансова діяльність; financial activity; финансовая деятельность; українські землі; Ukrainian lands; украинские земли; Російська імперія; Russian Empire; Российская империя; фінансовий контроль; financial control; финансовый контроль; державне регулювання фінансів; state regulation of finances; государственное регулирование финансов; 081 – Право